The Moderating Role of Financial Literacy and Gender on The Effect of Overconfidence And Present Bias on MSME Financial Decision-Making In Bandung City, Indonesia - Heraeni Tanuatmodjo; Asep Kurniawan; Badria Muntashofi; Laely Purnamasari; Imas Purnamasari; Pitri Yanti (Jurnal Ekuisci, 2026)
Background. Behavioral finance research has so far focused largely on capital-market investors in developed countries, while understanding of how overconfidence and present bias shape the financial decisions of Micro, Small, and Medium Enterprise (MSME) owners in developing countries particularly the protective role of financial literacy and gender as moderators remains limited and yields inconsistent findings across contexts. Aims. This study addresses that gap by examining the effect of overconfidence and present bias on financial decision-making among 388 MSME owners in Bandung City, Indonesia, with financial literacy and gender as moderating variables. Methods. Using Moderated Regression Analysis (MRA), the results show that overconfidence (β=-0.324, p<0.001) and present bias (β=-0.581, p<0.001) both have a significant negative effect on the quality of financial decision-making. Result. Financial literacy moderates the effect of overconfidence (β=-0.026, p=0.035) but does not moderate the effect of present bias (p=0.999)  a pattern that contrasts with some findings among individual investors in Pakistan and Saudi Arabia. Gender is not found to moderate either relationship (p>0.05), diverging from the classic finding of Barber and Odean (2001) in the United States investor context. Conclusion. These findings indicate that the effectiveness of financial literacy as a protective factor is bias-specific rather than bias-general, with important implications for the design of financial literacy interventions for the MSME sector in developing countries.